Evaluation of EQ4KIDZ, an emotional intelligence program for primary school children in Western Australia - Oliver, Lynnette Caroline (Curtin University, 2011)
Historically, schools have deemed cognitive skills more important than social and emotional skills for academic success. However, present research suggests that emotional intelligence (EI) may be more important than intelligence quotient (IQ) for success in both schools and the workplaces because of the social nature of emotional intelligence. The originators of the theory of emotional intelligence assert that emotional intelligence can be developed and can play a major role in fulfilling successful social interactions. The concept that IQ may not be as important for success in life as EI (known also as EQ) has resulted in the emergence of many emotional intelligence training programs in both the workforce and for school aged children. EI theorists contend emotional awareness lessons can assist children to understand their own emotions and emotions in others to achieve positive outcomes.The main objective of this research was to ascertain whether emotional intelligence can be developed in primary school age children and whether it does enable them to achieve academic outcomes more successfully than they were demonstrating prior to the implementation of the program. The study was conducted using a small group of primary school children who attended an established emotional development program known as EQ4KIDZ.The results of this research strongly supported the literature in that the EQ4KIDZ program was an emotional intelligence developer, with all participants rating EQ4KIDZ as highly effective for teaching emotional intelligence skills. Both parents and teachers reported noticeable changes after the children had completed EQ4KIDZ. The program taught the skills that made the learner confident, motivated, aware of expected behaviours, able to manage personal impulses, able to seek help when appropriate, wait a turn, be aware and effectively interact with others. The program also had positive effects on most of the children's behaviours- emotionally, socially, academically and promoting positive relationships within their respective schools, homes and the broader community.Although teachers, parents and students in this research recommended EQ4KIDZ to be incorporated into a school curriculum and with the data results indicating EQ4KIDZ could be very successfully implemented into a school curriculum, there would need to be a firm commitment by educational leaders as well as financial support by the Department of Education of Western Australia for ongoing student success. The outcomes from this study then have broad implications for effective educational practices.